Kriteria pemilihan kakitangan akademik IPTS menggunakan teknik sentroid tertib pangkat - Ahmad Mahir Razali ,; Ang , Chiu Woon (Penerbit ukm, 2007)
This study was carried out to determine the importance of each criterion and sub criteria that are considered during academic staff selection. This is a case study which was carried out from April to June 2005 at UNITEN, a private institution of higher education (PIHE) with university status. Interview was conducted with the human resource manager to find out about their academic staff selection procedure. Questionnaire was distributed to every decision maker (Dean, Deputy Dean, Head of Department) in academic staff selection. Ranking scale was used to rank the importance of the criteria and sub criteria. Then, weight value for each criterion and sub criteria was calculated using the rank order centroid technique. Analysis shows that academic qualification criterion has the highest weight (0.4207), followed by work experience (0.2039), teaching ability (0.2030), research activity (0.1108) and lastly personality (0.0618). In conclusion, decision makers can use these findings as additional information to be applied in the decision making process regarding selection of the academic staff